Akulturasi Budaya dan Penyebaran Islam di Banten Girang - Mahmudhatul Lutfiya Khasanah; Nuruzzalfa Aini; Fildzah Aulia Nur Muharromah; Ahmad Maftuh Sujana (Jurnal Kajian Islam dan Sosial Keagamaan, 2025)
The Banten Girang site is one of the important historical relics in Banten Province. This location is known as a spiritual hermitage that reflects the traditions and beliefs of the local people. Before the arrival of Islam, the site showed the strong influence of Hindu-Buddhist culture. However, with the entry of Islam in the 16th century, there was a significant transformation in the religious practices of the community. This study aims to examine the dynamics of acculturation of local culture with Islamic teachings in Banten Girang. This study uses a qualitative descriptive method with a literature study and historical analysis approach. The results of the study show that the Islamization process in Banten does not erase local culture, but interacts harmoniously with existing traditions. Islam in Banten developed with a peaceful approach, thus creating religious practices that were distinctive and adaptive to the local culture. This research emphasizes the importance of a cultural approach in Islamic da'wah, both in the past and as a lesson in the context of today's da'wah.